Respuesta :
Answer:
x = 3.
Step-by-step explanation:
log4 (3x - 1) = log4 (x + 5) Since they are both logs to the base 4:
3x - 1 = x + 5
2x = 6
x = 3.
On solving the logarithmic equation, we find that x = 3.
What are logarithmic equations?
A logarithmic equation is an equation that involves the logarithm of an expression containing a variable.
[tex]log_{4}(3x-1) = log_{4}(x+5)\\\\3x-1 = x+5\\\\3x-x=5+1\\\\ 2x=6\\\\x=3[/tex]
Learn more about logarithmic equations here
https://brainly.com/question/14411000
#SPJ3